AZD6738 Inhibits fibrotic response of conjunctival fibroblasts by regulating checkpoint kinase 1/P53 and PI3K/AKT pathways - Huang, Longxiang; Ye, Qin; Lan, Chunlin; Wang, Xiaohui; Zhu, Yihua (Frontiers in Pharmacology, 2022)
Trabeculectomy can effectively reduce intraocular pressure (IOP) in glaucoma patients, the long-term surgical failure is due to the excessive proliferation and fibrotic response of conjunctival fibroblasts which causes the subconjunctival scar and non-functional filtering bleb. In this study, we demonstrated that AZD6738 (Ceralasertib), a novel potent ataxia telangiectasia and Rad3-related (ATR) kinase inhibitor, can inhibit the fibrotic response of conjunctival fibroblasts for the first time. Our in vitro study demonstrated that AZD6738 inhibited the level and the phosphorylation of checkpoint kinase 1 (CHK1), reduced TGF-β1-induced cell proliferation and migration, and induced apoptosis of human conjunctival fibroblasts (HConFs) in the high-dose group (5 μM). Low-dose AZD6738 (0.1 μM) inhibited the phosphorylation of CHK1 and reduce fibrotic response but did not promote apoptosis of HConFs. Further molecular research indicated that AZD6738 regulates survival and apoptosis of HConFs by balancing the CHK1/P53 and PI3K/AKT pathways, and inhibiting TGF-β1-induced fibrotic response including myofibroblast activation and relative extracellular matrix (ECM) protein synthesis such as fibronectin (FN), collagen Ⅰ (COL1) and collagen Ⅳ (COL4) through a dual pharmacological mechanism. Hence, our results show that AZD6738 inhibits fibrotic responses in cultured HConFs in vitro and may become a potential therapeutic option for anti-subconjunctival scarring after trabeculectomy.